PS-B12-7: PERSISTENT REDUCTION IN RENAL RENIN FOLLOWING EARLY TREATMENT OF SPONTANEOUSLY HYPERTENSIVE RATS WITH LOSARTAN. (January 2023) - Harrap, Stephen; Suphapimol, Vera; Byars, Sean; De Vries, Nathan; Prestes, Priscilla; WilkinsonBerka, Jenny; Charchar, Fadi
Abstract : Objective: Abnormalities of renin-angiotensin system (RAS) and renal function have been reported in young spontaneously hypertensive rats (SHR) and blood pressure (BP) can be permanently reset to lower levels after brief early treatment with RAS inhibitors. We sought to determine whether renal renin was affected long-term by early RAS blockade. Design: Male SHR were treated via minipump from 10–14 weeks of age with vehicle (Veh, n = 12) or losartan (Los, n = 14, 7.5 mg/kg/d). Four Veh and six Los SHR were culled at 14-weeks and the remaining animals at 20-weeks. To control for effects of low BP another group received hydralazine (HZ, n = 6, 1 mg/kg/d) from 10–20 weeks. Methods: At 14- and 20-weeks systolic BP was measured, and kidneys collected. Three micrometer paraffin sections of renal cortices were counterstained with hematoxylin for renin immunolabelling, assessed for each animal as the percentage of labelling in 200 glomeruli which displayed the afferent arteriole entering the glomerulus. Results: At 14-weeks the systolic BP (mean ± SEM) was significantly (P < 0.001 by ANOVA) lower in both the Los (145 ± 7 mmHg) and HZ (153 ± 7 mmHg) SHR compared with Veh (206 ± 6 mmHg). At 20-weeks, the same pattern persisted (Los: 187 ± 6 mmHg; HZ: (155 ± 4 mmHg; Veh: 220 ± 6 mmHg) (P < 0.001 by ANOVA). Renal renin immunolabelling increased dramatically during treatment at 14-weeks (44.8 ± 1.1%) compared with Veh (10.5 ± 1.7%) (P < 0.0001 by ANOVA). However, at 20-weeks renal renin was significantly lower in Los (7.7 ± 0.9%) (P < 0.05 by ANOVA) compared with Veh (11.9 ± 1.2%), while renal renin was significantly higher in HZ kidneys (18.0 ± 1.0%) than both Los and Veh kidneys (P < 0.01 by ANOVA). Conclusions: The persistently low BP in SHR following brief early treatment with losartan is associated with reduced renal renin. Normally one would expect activation of the renal RAS with lower BP, as observed with the hydralazine-treated SHR. These results suggest that long-term reduction in renal renin following brief early RAS blockade in SHR might cause the persistently reduced BP seen in these animals.